Expert System For Autism Prediction in Children With Web-Based Forward Chaining Method: Expert System For Autism Prediction in Children With Web-Based Forward Chaining Method - Topan Yulianto; Septi Andryana; Aris Gunaryati (Institute of Computer Science (IOCS), 2020)
Autism is one of the categories of children with special needs, namely brain nerve development disorders that affect the ability to communicate and interact socially. Autism is divided into 5 types: Autistic Disorder, Asperger's Disorder, Perspective Developmental Disorder-Not Otherwise Specified (PDD-NOS), Rett's Disorder, Childhood Disintegrative Disorder (CDD). This research was conducted to predict the type of autism that occurs in children using a web-based expert system with the method of forward chaining, using data collected through various sources about autism. The data will be implemented into the system, so the system can provide information about the types of autism that exist, as well as the symptoms experienced by each type of autism. This system will also be able to diagnose patients by giving a number of questions to the symptoms that occur then providing appropriate treatment solutions through various therapies.